Compatibility of the selective area growth of GaN nanowires on AlN-buffered Si substrates with the operation of light emitting diodes. (6th February 2015) - Musolino, M; Tahraoui, A; Fernández-Garrido, S; Brandt, O; Trampert, A; Geelhaar, L; Riechert, H
Abstract: AlN layers with thicknesses between 2 and 14 nm were grown on Si(111) substrates by molecular beam epitaxy. The effect of the AlN layer thickness on the morphology and nucleation time of spontaneously formed GaN nanowires (NWs) was investigated by scanning electron microscopy and line-of-sight quadrupole mass spectrometry, respectively. We observed that the alignment of the NWs grown on these layers improves with increasing layer thickness while their nucleation time decreases. Our results show that 4 nm is the smallest thickness of the AlN layer that allows the growth of well-aligned NWs with short nucleation time. Such an AlN buffer layer was successfully employed, together with a patterned SiO x mask, for the selective-area growth (SAG) of vertical GaN NWs. In addition, we fabricated light-emitting diodes (LEDs) from NW ensembles that were grown by means of self-organization phenomena on bare and on AlN-buffered Si substrates. A careful characterization of the optoelectronic properties of the two devices showed that the performance of NW-LEDs on bare and AlN-buffered Si is similar. Electrical conduction across the AlN buffer is facilitated by a high number of grain boundaries that were revealed by transmission electron microscopy. These results demonstrate that grainy AlN buffer layers on Si are compatible both with the SAG of GaN NWs and LED operation. Therefore, this study is a first step towards the fabrication of LEDs on Si substrates based on homogeneous NW ensembles.